Manipulation of Multielectron Dynamics of Molecules by Fourier-Synthesized Intense Laser Pulses: Effective Potential Analysis of CO - Ohmura, Shu; Ohmura, Hideki; Kato, Tsuyoshi; Kono, Hirohiko (Frontiers in Physics, 2021)
We present a theoretical investigation as to how multielectron dynamics of CO are manipulated by Fourier-synthesized intense laser pulses. The pulses used are assumed to be comprised of harmonics up to the fourth order. The multiconfiguration time-dependent (TD) Hartree-Fock (MCTDHF) method, where the multielectron wavefunction is expressed as a linear combination of various electron configurations, is employed to simulate the dynamics of CO interacting with Fourier-synthesized pulses. The multielectron nature such as electron correlation is quantified by using our effective potential approach. To begin with, the time-dependent natural orbitals which diagonalize the first order reduced density matrix are obtained from the MCTDHF wave function. The effective potentials that determine the dynamics of natural orbitals are then derived, which consists of the one-body part including the interaction with the laser electric field and the two-body part originating from electron-electron interaction. The role of electron correlation can be quantified by comparing the effective potentials obtained with those obtained by the TDHF method. We found a very similar profile in the effective potential of the 5sigma highest occupied molecular orbital (HOMO) for one-color (omega) and directionally asymmetric omega +2omega two-color pulses; when the electric field points from C to O, a hump (or shoulder) appears in the effective potential only 2 bohrs outward from C. The hump formation, which originates from the field-induced change in the two-body part (especially, due to electron correlation), is responsible for experimentally observed anisotropic ionization from the C atom side. A coherent superposition of omega and 2omega fields with an appropriate relative phase works as a one-color pulse of which either positive or negative peaks are filtered out. More sophisticated manipulation is possible by adding higher harmonics to a synthesized field. We show that the 5sigma orbital can be squeezed toward the inside of the valley in the effective potential, which encloses the molecule at a radius of 7 bohrs (semicircle in the region of z <0), by adjusting the phases of a four-color field. We found that hump and valley formation in the effective potential are closely correlated with domains of increasing and decreasing electron density, respectively.